2021
DOI: 10.1182/blood.2020008865
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of corticosteroids on efficacy of chimeric antigen receptor T-cell therapy in large B-cell lymphoma

Abstract: Corticosteroids are commonly used for the management of severe toxicities associated with chimeric antigen receptor (CAR) T-cell therapy. However, it remains unclear whether their dose, duration, and timing may impact clinical efficacy. Here, we determined the impact of corticosteroids on clinical outcomes in patients with relapsed or refractory large B-cell lymphoma treated with standard of care anti-CD19 CAR T-cell therapy. Among 100 patients evaluated, 60 (60%) received corticosteroids for management of CAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(114 citation statements)
references
References 22 publications
4
98
0
1
Order By: Relevance
“…Our study found that if only according to the glucocorticoids use for investigating its impact on the efficacy of CAR-T cell therapy generally drew negative conclusions. When the cumulative dose, duration and timing of glucocorticoids were further analyzed, a study found that high-dose glucocorticoids were associated with shorter PFS, and the high dose, prolonged duration, and timing all significantly impacted OS of patients (25). But another study of which major drawback was the undefined cut-off value indicated that the dose and duration of glucocorticoids had no effect on PFS and OS (26).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our study found that if only according to the glucocorticoids use for investigating its impact on the efficacy of CAR-T cell therapy generally drew negative conclusions. When the cumulative dose, duration and timing of glucocorticoids were further analyzed, a study found that high-dose glucocorticoids were associated with shorter PFS, and the high dose, prolonged duration, and timing all significantly impacted OS of patients (25). But another study of which major drawback was the undefined cut-off value indicated that the dose and duration of glucocorticoids had no effect on PFS and OS (26).…”
Section: Discussionmentioning
confidence: 99%
“…There was only one eligible controlled study that specifically investigated patients receiving glucocorticoids as an intervention after Axi-cel therapy, which may be due to the limited clinical experience and treatment options available for ICANS management and the need for emergency treatment following adverse reactions in patients (25). Therefore, all the studies we included were retrospective studies or case reports.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations